ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PADA SEKTOR PERHOTELAN DI PROVINSI MALUKU DENGAN MENGGUNAKAN METODE REGRESI DATA PANEL - Muhammad Yahya Matdoan; Mozart W Talakua (LPPM Universitas Terbuka, 2021)
The hotel sector is one of the sectors that has made a major contribution to employment and economic development in Maluku Province. The more the population, the more difficult it is to find work. The purpose of this study is to analyze the effect of the variable number of accommodation, number of occupancy, number of available beds and minimum wage of employees on labor absorption in the hotel sector in Maluku Province. One method that can be used to solve this problem is the Panel Data Regression method. Panel data regression is a combination of time series data and cross section data. This method can be used to determine the relationship between two or more variables that are quantitative in nature, so that one variable can be predicted from the other variables. The Panel Data Regression model used in this study is the Fixed Effect Model (FEM) with the results obtained, namely that there are three variables that affect labor absorption in the hotel sector in Maluku Province, namely the number of accommodation, the number of occupancy and the minimum wage of employees. Meanwhile, the number of available beds has no effect on labor absorption in the hotel sector in Maluku Province.